2022
DOI: 10.1051/0004-6361/202244222
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dust production and mass loss in the AGB phase using post-AGB stars in the Magellanic Clouds

Abstract: Context. The asymptotic giant branch (AGB) phase of evolution in low-and intermediate-mass stars is governed by poorly understood physical mechanisms, such as convection, mixing, dust production and mass loss, which play a crucial role on determining the internal structure and the evolution of these stars. The spectra of post-asymptotic giant branch (post-AGB) stars hold critical chemical fingerprints that serve as exquisite tracers of the evolution, nucleosynthesis, and dust production during the AGB phase. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…By and large, theoretical single-star low-mass AGB models are in agreement with observations (e.g. van Aarle et al 2011;De Smedt et al 2014, 2016. However, a study by Kamath et al (2017) reported a subset of luminous single post-AGB stars (one in the Small Magellanic Cloud (SMC) and two in the Galaxy) that exhibited neither traces of carbon enhancements nor s-process elements, suggesting a likely failure of the third dredge-up (TDU).…”
Section: Introductionsupporting
confidence: 70%
“…By and large, theoretical single-star low-mass AGB models are in agreement with observations (e.g. van Aarle et al 2011;De Smedt et al 2014, 2016. However, a study by Kamath et al (2017) reported a subset of luminous single post-AGB stars (one in the Small Magellanic Cloud (SMC) and two in the Galaxy) that exhibited neither traces of carbon enhancements nor s-process elements, suggesting a likely failure of the third dredge-up (TDU).…”
Section: Introductionsupporting
confidence: 70%
“…This estimate must be considered as an upper limit of the duration of this phase; indeed the recent works on the AGB to post-AGB transition by refs. 79,80 showed that to reproduce the IR excess of post-AGB stars in the Galaxy and in the Magellanic Clouds one has to invoke significantly higher mass-loss rates than those based on the aforementioned formulations, something that would reduce the timescales by a factor of about five. The timescale of 10,000 yr is therefore easily reconciled with the observed timescale of 2,200-5,700 yr implied by the nebula.…”
Section: Photoionization Modellingmentioning
confidence: 99%